Quick Of Blood dan Ultrafiltrasi Terhadap Nilai Ureum Pada Pasien Hemodialisis - Ita Ulva Hanivah; Santi Herlina (UIMA Press, 2019)
Patients with hemodialysis (HD) need to be assessed for their HD adhesions periodically. One parameter of adequation of HD action is to measure the values of Ureum to know the Ureum reduction ratio (URR). The purpose of this research is to know the relation of quick of blood (QB) and ultrafiltration (UF) to urea value in hemodialysis patient at Klinik Klinik Khusus Hemodialisa Sahabat Keluarga. This study was conducted on 68 respondents (accidental sampling) using medical record data and written on the questionnaire. The result of the first measurement is known that the QB relations with ureum post HD value has weak relation and negative pattern (r = 0,049), and P Value 0,034 (α 0,05), so it can be concluded that there is a QB relations to ureum value. In the second measurement analysis, the result of QB relationsh with ureum value of post HD has a weak and negative correlation (r = 0,187), and the second measurement is P value 0,127 (α 0,05), so it can be concluded there is no relation of QB to value of ureum. The result of first measurement is known that UF relationship with ureum post HD value has weak relation and negative pattern (r = 0,220), and P Value 0,071 (α 0,05) found no relation of UF to ureum value. In the second measurement, the result of UF relations with ureum value of post HD has moderate and negative relationship (r = 0,335), and the second measurement is P value 0,005 (α 0,05), so it can be concluded that there is UF relation to value ureum.